The Safety and Health Management at Highway Construction Site in Malaysia - RAMASAMY, KESSHALA; ALI TIGHNAVARD BALASBANEH, (Recent Trends in Civil Engineering and Built Environment, 2023)
The construction industry is one of the most dangerous and high-riskwork industry in the world. Therefore, safety and health management at highwayconstruction is not applied systematically, accidents will arise, its will literallyaffect to Malaysia’s economic growth in future .Moreover, highway constructioncarry significant risks.The most common factors that contribute to these risksinclude inefficient planning, unexpected delays, poor quality equipment , andinadequate oversight.A questionnaire survey was conducted, targeting respondentswho are highway projects under construction at Wilayah Persekutuan KualaLumpur.To determine respondent demographics, descriptive data were examinedusing a frequency and percent distribution. During this period, the mean score andRelative Importance Index were used to describe consensus on health and safetymanagement in highway construction (RII). The findings of this study will assistpractitioners in paying greater attention to health and safety management issues thatwill effect the success of security and health management for highway buildingprojects.